THE USE OF GEN Z SLANG BY DIGITAL INFLUENCER "AWKARIN" ON HER SOCIAL MEDIA: A SOCIO-SEMANTIC STUDY - Khairunissa, Meilita; Budiwati, Tri Rina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Generation Z increasingly relies on slang as a linguistic resource to express identity, negotiate belonging, and build intimacy in digital communication, making it an important site of sociolinguistic and semantic change. However, most existing studies focus on broad usage patterns rather than examining how individual influencers strategically use slang to construct their online personas. Addressing this gap, this study analyzes Awkarin’s use of Gen Z slang on Instagram and YouTube through a qualitative sociolinguistic and semantic approach. The analysis identifies various slang forms—such as acronyms, neologisms, semantic shifts, and code-mixing—and their communicative functions in shaping influencer–audience interaction. Findings reveal that slang serves not only as informal vocabulary but as a strategic resource for identity performance, emotional expression, and audience engagement. This study contributes to sociolinguistic and semantic research by showing how influencers act as linguistic mediators who adapt and circulate Gen Z slang within Indonesian digital culture, highlighting slang as both a social practice and a site of meaning innovation.